Taxing the hard-to-tax lessons from theory and practice. - Alm, James Robert; Martinez-Vazquez, Jorge (Emerald, 2005)
The goal of this edited volume is to take a hard, objective look at the many different aspects of taxing the hard-to-tax, as well as the many different approaches that have been employed around the world. In the developed and developing world, taxing certain kinds of activities, sectors, or individuals - the so-called hard-to-tax - is a challenge for governments. In the past, the practical side of this issue has received some attention, mainly from those working in the trenches of tax administration. There has also been some analytical work on such things as presumptive taxation, as well as some empirical work on measuring the hard-to-tax. However, the lessons from all of this work have been very unevenly disseminated, and there are clearly many unresolved issues. With the steady advance of such things as globalization, internet commerce, and tax shelters, the issues in taxing the hard-to-tax will become even more pressing.
Keywords: Monetary policy.; Mathematical analysis.; elektronické knihy; electronic books